(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents the design and simulation of broadband microstrip patch antenna using High Frequency Structure Simulator (HFSS).The two different configuration of broadband microstrip patch antenna, simple rectangular patch antenna & E shaped patch antenna are analyzed. The performance of designed antennas is analyzed in terms of return loss, bandwidth and gain. The substrate used in these two configurations is FR-4 having dielectric constant 4.4. After analyzing, the return losses and gain of two different antennas are calculated. The calculated result for return loss of rectangular patch & E shape patch are -21.93 db & -25.714 db and gain of rectangular patch & E shape patch are 6.787 db & 8.284db respectively